Brief communication: Rapid acceleration of the Brunt Ice Shelf after calving of iceberg A-81 - Marsh, Oliver J.; Luckman, Adrian J.; Hodgson, Dominic A. (The cryosphere, 2024)
The Brunt Ice Shelf, Antarctica, accelerated rapidly from a velocity of 900 to 1500 m a−1 during 6 months, following calving of a 1500 km2 iceberg on 22 January 2023. The immediate response to calving was observed as a change to the rate of acceleration and not to velocity directly. Acceleration increased by a factor of 10, with a second, smaller calving at the end of June 2023, leading to further tripling of acceleration. The acceleration was caused by the reduction of buttressing at the McDonald Ice Rumples, leading to high localised strain rates, which reduce the strength of the remaining ice shelf.